The venture capitalist's cognitive approach: Validation through the Tunisian context - Dziri Houda; Jarboui Anis (Cogent Economics & Finance, 2017)
This study is aimed to examine the major determinants of cognitive approach investigated with according to a set of 150 firms financed by Tunisian venture capital agencies observed over the period 2010-2015. We are led to conclude that some venture capitalist's characters do appear to affect the cognitive contribution within funded firms. In addition, it has been revealed that the manager's share held, the venture capitalist' participation in the capital and the firm age appear to have a significant influence on the cognitive approach adopted by the venture capital.
Keywords: 330; cognitive resources; ownership structure; venture capital